Линейные системы автоматического регулирования (анализ) - Извольский Евгений Георгиевич (1974)
Экземпляры: КХ (20170918) / Инвентарный номер: 605922 / Сис.шифр: 621.38 / Авт.знак: И 34 / ГРНТИ: 50 / ББК: 32